KEMAMPUAN MAHASISWA PGSD DALAM MENYELESAIKAN SQAL-SOAL MATEMATLKA SD - P. Sarjiman, P. Sarjiman (LPPMP Universitas Negeri Yogyakarta, 2002)
This article is based on a research conducted to find out (1)D-II PGSD students' levelofability in solving elementary schoolmathematical problems (D-II PGSD is a course program training elementary school teachersof mathematics), (2) the functional correlation between their motivation for achievement aswell as their experience (which covers former high school, lengthof time in teaching at elementary school, and frequency in attending upgrading sessions) and their levelofability in solvingelementary school mathematical problems, and (3) the contributiongiven bytheir motivation for achievement together with theirexperience to their levelofability in solving elementary schoolmathematical problems.From the total populationof 135 students ofD-II PGSD inthe academic year of2000/2001, a sample consisting ofsixty-sixstudents was taken by meansofsimple random sampling. A questionnaire and a test were administered to obtain the data, on whichzero order correlation, partial correlation, and multiple regres.sion analyses were conducted It was found that they w(lre able to solve 73.4% of all theelementary schoolmatheplatical problems presented, an achievement categorized poor because they were formally consideredelementary schooI teacher candidates. The percentage found fortheir motivation for achievement was 70.5%, which was categorized good. They were categorized low in experience in the academic yearof2000/200I and the average percentage oftheir experience was 59.06%. The resultsof the zero order and partialcorrelation analyses showed that there was a positive and significant correlation between their motivation for achievement aswell as their experience and their levelof ability in solvingelementary school mathematical problems(r